Efektivitas Pemanfaatan Media Facebook pada Laman Notifikasi Beranda untuk Meningkatkan Kemampuan Menulis Puisi Siswa Kelas X SMA Nurul Iman: Efektivitas Dalam Pemanfaatan Media Facebook - Fadhilla Pratiwi; Dra. Rosmawati Harahap.,M.Pd.,Ph.D. (Medan Resource Center, 2023)
The research was carried out which aims to describe the use, application, and use of facebook media on the notification page of the homepage in writing poetry by students of class X SMA Nurul Iman. This study uses a quantitative descriptive method with a population of 180 people and a set sample of 27 people. The total sample is 15% of the total population. The highest score obtained is 90 while the lowest score is 75. Based on the results of data analysis, the average utilization, application, and use of facebook media on the notification page homepage by class X SMA Nurul Iman students is 81.85 (85%) which is categorized as